2014
DOI: 10.1097/01.tp.0000437432.35227.3e
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of BK Viremia in Kidney Transplant Recipients

Abstract: The results showed increased activity of cytotoxic T cells and natural killer cells in BKVN and viremia samples resembling acute rejection and suggested the involvement of both adaptive and innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Studies of gene expression during BK viremia and BKN have shown upregulation of cytotoxic T cell as well as NK cell-associated transcripts (20). In contrast to the predominantly CD8+ T cell response observed in our study, other investigators have found the polyfunctional CD4+ T cell response to be upregulated during viral replication (21,22), which may be related to measurement of T cell function after resolution of viremia, as CD4+ has been shown to be associated with maintenance of viral control (13).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of gene expression during BK viremia and BKN have shown upregulation of cytotoxic T cell as well as NK cell-associated transcripts (20). In contrast to the predominantly CD8+ T cell response observed in our study, other investigators have found the polyfunctional CD4+ T cell response to be upregulated during viral replication (21,22), which may be related to measurement of T cell function after resolution of viremia, as CD4+ has been shown to be associated with maintenance of viral control (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation using highthroughput microarray analysis of PVAN/TCMR tissue allograft samples to significantly enrich the genomic picture of these pathological features is scarce. Recently, Lubetzky et al 12 investigated the genomics of PVAN, mainly in whole blood and in a reduced number of tissue allograft samples by microarray analysis. Authors reported a significantly increased pathogenesis-based transcript activity of cytotoxic T cells and natural killer cells in PVAN resembling TCMR, suggesting the involvement of adaptive and innate immunity in both settings.…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence of T cell activation during viremia or PVAN includes the expression of mRNA associated with a cytotoxic program in T cells. 76 …”
Section: Immunology Of Pvanmentioning
confidence: 99%
“…There is an inflammatory response resembling histologically and genetically to acute rejection. 76,86 Whether this response is appropriate or is overwhelming, as an immune reconstitution syndrome, is not known. Two questions remain, does this process trigger fibrosis 87 and/or allospecific damage ?…”
Section: Immunology Of Pvanmentioning
confidence: 99%
See 1 more Smart Citation